Importations et imitations de céramiques de l’Ouest de la Gaule au second âge du Fer en Île-de-France - Jean-Marc Séguier (Revue Archéologique du Centre de la France)
The recent discovery in the Île-de-France of imported pottery (sherds with stamped decoration), but also of possible copies of storage jars, or even three-legged tubs in privileged contexts and in a funerary complex, raises the question of links that could unite the Paris Basin to the west of Gaul at the end of the early / middle La Tène periods. The studied elements take on different meanings, but appear part of the same movement, the extent and nature of which are certainly difficult to assess, but cannot be ignored. The question of the distribution of salt is considered without which the track can be considered exclusive.